2014
DOI: 10.1016/j.drugalcdep.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use and achievement of abstinence from alcohol and other drugs among people with substance dependence: A prospective cohort study

Abstract: Background Many with alcohol and other drug dependence have concurrent marijuana use, yet it is not clear how to address it during addiction treatment. This is partially due to the lack of clarity about whether marijuana use impacts one’s ability to achieve abstinence from the target of addiction treatment. We examined the association between marijuana use and abstinence from other substances among individuals with substance dependence. Methods A secondary analysis of the Addiction Health Evaluation And Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
6
26
1
Order By: Relevance
“…That we did not find marijuana to be a risk factor for continued heavy drinking despite intervention is worth noting, as two other studies found marijuana to be associated with worse drinking outcomes (Aharonovich et al, 2005; Mojarrad et al, 2014). Several explanations may account for our finding.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…That we did not find marijuana to be a risk factor for continued heavy drinking despite intervention is worth noting, as two other studies found marijuana to be associated with worse drinking outcomes (Aharonovich et al, 2005; Mojarrad et al, 2014). Several explanations may account for our finding.…”
Section: Discussionsupporting
confidence: 42%
“…Regarding marijuana’s effects, Aharonovich et al (2005) showed that marijuana use after discharge from inpatient substance abuse treatment was associated with higher likelihood of relapse to alcohol use. Similarly, Mojarrad et al (2014) found that baseline marijuana use reduced substance abstinence after outpatient substance abuse treatment, with no difference in effect by dependence type (i.e., alcohol, drugs, both). That comorbid drug use is associated with less successful alcohol outcomes following treatment in several studies may reflect drug interference with engagement in treatment (Mitchell and Selmes, 2007), or drug-related impairments in ability to manage drinking behavior (e.g., impairment in self-regulation of impulses and cravings; Pani et al, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…Concurrent use of marijuana and alcohol is associated with heavy episodic drinking, and the combined use of cannabis and alcohol may lead to more substance use and related problems compared to the use of alcohol alone . Cannabis use has been examined as a predictor of substance use outcomes in a few treatment studies , and was found to have a deleterious impact.…”
Section: Introductionmentioning
confidence: 99%
“…95,136–141 The literature supports the premise that previous substance abuse may be associated with prescription opioid use 139 and that the use of prescription opioids may in turn be associated with substance abuse. 138,140,141 The use of heroin was associated with previous use of prescription opioids among 75% of 18 to 25-year-old respondents in a retrospective cohort of subjects admitted for substance abuse treatment. 138 In a cross-sectional study among adolescents, both medical users (6%) and nonmedical users (65.9%) of opioids reported more substance abuse than those who had never used opioids ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%